PHYSICAL ACTIVITY LEVEL EATING HABITS AND NUTRITIONAL STATUS IN SCHOOL ZONES URBAN AND RURAL PIRIPIRI-PI. (Fiep Bulletin - online, 2016)
Introduction: Overweight and obesity are among the most serious problems of rich countries and emerging countries. The problems arising directly or indirectly from obesity are responsible for a significant percentage of deaths. This study aims to verify and compare the level of physical activity (LPA), Food Habits (HA) and nutritional status, in students from urban and rural areas of the municipality of Piripiri-PI. Methods: Cross-sectional study of descriptive and quantitative type. To collect the anthropometric indicators, we used a handmade stadiometer and a digital scale; For verifying the physical activity level of students we used the IPAQ (short version); To evaluate the dietary habits was used a questionnaire validated by CIRILLO, 2008. For comparison between urban and rural groups used the chi-square test adopting the significance level of p
Keywords: physical activity; obesity; IPAQ; BMI